2019
DOI: 10.14686/buefad.566640
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Preservice Teachers’ Levels of Metacognitive Awareness in Terms of Certain Variables

Abstract: This study focuses on metacognition and has two main purposes: (1) to determine preservice teachers’ levels of metacognitive awareness and (2) to determine how they relate to the variables of academic achievement, gender, grade level and department. The participants were biology, physics and chemistry preservice teachers (N=367). The Metacognitive Awareness Inventory (MAI) was used as a data collection tool for determining the preservice teachers’ metacognitive awareness. This is an associational survey study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(98 reference statements)
0
3
1
1
Order By: Relevance
“…Previous studies although dealing with pre-service teachers also found statistically non-significant gender differences in teachers' metacognitive awareness (Alci and Karatas 2011;Ekici et al 2019). The current findings show that background factors of gender, experience, and level of education have little influence on the inservice teachers' perceptions of metacognition.…”
Section: Background Factors and Teachers' Perceptionscontrasting
confidence: 46%
See 1 more Smart Citation
“…Previous studies although dealing with pre-service teachers also found statistically non-significant gender differences in teachers' metacognitive awareness (Alci and Karatas 2011;Ekici et al 2019). The current findings show that background factors of gender, experience, and level of education have little influence on the inservice teachers' perceptions of metacognition.…”
Section: Background Factors and Teachers' Perceptionscontrasting
confidence: 46%
“…However, no significant gender differences among the pre-service teachers were found by Usher (2019). Likewise in the study carried out by Ekici et al (2019), the pre-service male and female teachers had similar perceptions of their metacognition. Ibrahim and Watts (2016) too observed that males and females had similar perceptions of their metacognitive skills.…”
Section: Metacognition and Background Factors (Gender Teaching Experi...mentioning
confidence: 72%
“…In summary, Metacognitive Awareness Skills were found to predict academic achievement positively. In the literature; Ataalkın (2012), Alkan and Açıkyıldız (2020), Bağçeci et al (2011), Ekici, Ulutaş andAtasoy (2019), Çalgıcı (2018), Çakır and Yaman (2015), Ghonsooly, Khajavy and Mahjobi (2014), Sökmen and Kılıç (2016) examined the effect of metacognitive awareness on academic achievement in their studies and, they found that it affected positively.…”
Section: Resultsmentioning
confidence: 99%
“…Bu sayede öğrenciler düşünme süreçlerini aktifleştirerek kendi öğrenmelerinden sorumlu olacağı gibi öğrencilerin akademik başarıları artacaktır. Akademik başarının yordayıcısı olan üstbilişsel farkındalık öğrencilerin ders kaygısı yaşamasına engel olacaktır (Bağçeci, Döş & Sarıca, 2011;Ekici, Ulutaş & Atasoy, 2019;Mert & Baş, 2019;Özturan-Sağırlı, Baş & Bekdemir, 2020).…”
Section: Introductionunclassified